ANALISIS SEKTOR EKONOMI UNGGULAN DI KABUPATEN SUMBAWA - Nining Sudiyarti; Bambang Darmansyah (Jurnal Ekonomi & Bisnis, 2023)
This study aims to know and analyze the leading sectors of the economy in Sumbawa District, which are competitive in economic growth. The type of this study was qualitative study. The data used was secondary data obtained from the Gross Regional Domestic Product of Sumbawa district and West Nusa Tenggara (NTB) Province in 2012-2017. The data analysis tool used was the analysis technique of Growth Ratio Model (MRP) and Klassen Typology. The results of the study showed based on Growth Ratio Model analysis (GRM) showed that there were several sectors that had positive growth in the study area and reference area, including the Wholesale and Retail Trade sector, Car and Motorcycle Repair and the information and communication sector. Meanwhile, the results of the Klassen typology showed that the economic sectors classified as superior sectors were the agriculture, forestry and fishery sectors; electricity and gas procurement sector; wholesale and retail trade, repair and maintenance of cars and motorcycles; and the education services sector. So, based on the results of the two analytical tools used, the conclusion were that the leading sectors in Sumbawa district were prominent sectors and the advanced sectors are agriculture, forestry and fisheries; wholesale and retail trade, repair of cars and motorcycles; electricity and gas procurement sector; and the education services sector.